Persistent viral infections and their role in heart disease - Kloc, Anna; Bardinath, Ashwin; Bhatta, Sagar (Frontiers in Microbiology, 2022)
Viral infections are the culprit of many diseases, including inflammation of the heart muscle, known as myocarditis. Acute myocarditis cases have been described in scientific literature, and viruses, such as Parvovirus B19, Coxsackievirus B3, or more recently, SARS-CoV-2, were the direct cause of cardiac inflammation. If not treated, myocarditis could progress to dilated cardiomyopathy, which permanently impairs the heart and limits a person’s lifespan. Accumulated evidence suggests that certain viruses may persist in cardiac tissue after the initial infection, which could open up the door to reactivation under favorable conditions. Whether this chronic infection contributes to, or initiates, cardiac damage over time, remains a pressing issue in the field of virus-induced heart pathology, and it is directly tied to patients’ treatment. Previously, large case studies found that a few viruses: parvovirus B19, coxsackievirus, adenovirus, human herpesvirus 6, cytomegalovirus and Epstein-Barr virus, are most commonly found in human endomyocardial biopsy samples derived from patients experiencing cardiac inflammation, or dilated cardiomyopathy. SARS-CoV-2 infection has also been shown to have cardiovascular consequences. This review examines the role of viral persistence in cardiac inflammation and heart disease, and discusses its implications for patients’ outcomes.